التوجهات الفكرية وقيمها الجمالية في تصميم المجوهرات المعاصرة - Sum ayah Abdel-Wahhab Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Many researchers theorized to study the intellectual trends and their aesthetic values ​​in contemporary jewelry design, as it is a phenomenon (temporal, spatial) that explains the gustatory and social variables of its holders based on the problem of plurality of designs, which led to the contemporary buyer losing the sense of spatial belonging and identity when acquiring contemporary jewelry. Research problem: What are the most important pillars and requirements of intellectual trends and their aesthetic values ​​in contemporary jewelry design? The importance of the research: shedding light on the relationship between the subject and the object, the fact that the subject expresses the objective aspects while the subject expresses the material factors in order to reach the building of an integrated design process. Research objective: to reach the foundations, requirements of intellectual trends and their aesthetic values ​​in contemporary jewelry design. Research limits: The research is limited by studying jewelery designs in Iraqi markets.